Goran Ohlin. Population Control and Economic Development. Development Centre Studies, no. 8 París, OECD, Development Centre, 1967. 138 p. - Urquidi, Víctor L. (El Colegio de México A.C., 1969)
GORAN OHLIN, Population Control and Economic Development. Development. Centre Studies, Núm. 8. París, OECD, Development Centre, 1967.